Sildenafil 25 mg ODT + Collagenase Clostridium hystoliticum vs Collagenase Clostridium hystoliticum Alone for the Management of Peyronie's Disease: A Matched-Pair Comparison Analysis. Issue 10 (20th September 2018) - Cocci, Andrea; Cito, Gianmartin; Urzì, Daniele; Minervini, Andrea; Di Maida, Fabrizio; Sessa, Francesco; Mari, Andrea; Campi, Riccardo; Falcone, Marco; Capece, Marco; Morelli, Girolamo; Cacciamani, Giovanni; et al.
Abstract: Introduction: The effectiveness of phosphodiesterase type 5 (PDE5) inhibitors over the conservative management of Peyronie's disease (PD) has been widely questioned. Aim: To determine the role of sildenafil 25 mg film formulation twice a day (S25 b.i.d.) in the improvement of curvature after treatment of collagenase of Clostridium hystoliticum (CCH) in penile curvature owing to PD. Methods: From April 2017 to April 2018, 161 consecutive patients were treated with S25 b.i.d. + CCH or CCH alone. Adjustment variables consisted of age, penile curvature, and the 15-question International Index of Erectile Function (IIEF-15) questionnaire at baseline using 1:1 propensity-score matching. Overall, 50 patients were considered subdivided into the following: 25 patients who received S25 b.i.d. + CCH (group A) and 25 who received CCH alone (group B). Patients received CCH injection using a shortened protocol and vacuum device in both groups. Main Outcome Measure: The primary outcome of the study was the change in penile curvature after treatment, and secondary outcomes were the change in sexual function (IIEF-15) and in the Peyronie's Disease Questionnaire (PDQ) and its subscores, PDQ-PS (psychosexual symptoms), PDQ-PP (penile pain), and PDQ-SB (symptom bother). Results: Overall, mean penile curvature was 47.0° (SD 21.88), the mean IIEF-EF (erectile function) was 23.56 (SD 4.10), and the mean PDQ was 27.06 (SD 13.55). After the treatment, we observed a mean change for penile curvature of 25.6 (SD 9.05) in group A and –25.6 (SD 9.7) in group B ( P < .01), for IIEF-EF of 2.28 (SD 2.33) in group A and 1.36 (SD 1.77) in group B ( P  = .03), for PDQ-PS of –3.04 (SD 2.95) in group A and of –2.12 (SD 2.06) in group B ( P  = .11), for PDQ-PP of –1.0 (SD 4.48) in group A and of –0.88 (SD 2.04) in group B ( P  = .60), for PDQ-SB of –5.84 (SD 4.58) in group A and of –4.16 (SD 4.45) in group B ( P  = .60), and for Female Sexual Function Index of 3.8 (SD 2.45) in group A and of 2.72 (SD 2.28) in group B ( P  = .14). We found a rate of global satisfaction of 70.83% in group A and of 84.0% in group B ( P  = .27). Clinical Implications: Addition of S25 b.i.d. to CCH is superior to CCH alone for improving penile curvature and erectile function. Strength & Limitations: This is the first study comparing sildenafil + CCH vs CCH alone for the treatment of PD. Lack of randomization and direct verification of appropriate use of penile modeling could be considered limitations. Conclusion: In this study, combination therapy was superior in terms of penile curvature and erectile dysfunction improvement.